The mediation role of key account management effectiveness on key account management practices and market performance - Wong, H. F. (Medwell Journals, 2016)
The implementation of KAM (KAM) increase market performance of organisations and achieve effectiveness. Nevertheless, the arguments on what determines KAM effectiveness and market performance are unresolved due to inconclusive literature evidences. Thus, this study aims to propose a conceptual framework of the determinants that affect the KAM effectiveness and market performance. It has been confirmed that top management involvement, inter-functional coordination and formalization play an important role. Therefore, this paper extends the existing literature by introducing these dimensions to the framework of KAM. It is recommended that future survey can be conducted to investigate the significance of these factors.